An Overview of Demand Response Applications under Smart Grid Concept - Elma, Onur; Selamogullari, Ugur Savas (IEEE, 2017)
The idea of controlling the demand side electrical consumption has led the dissemination of demand response applications under smart grid concept. Especially residential demand response applications have been widely adopted and many studies have been conducted in the world. In this study general information about demand response is given and demand response research in the world and in Turkey is summarized. A simulation study is completed to show the effect of demand response application in a residential house using load shifting. In the simulation study, electrical appliances, which are intended to be used at high priced hours, are shifted forward in time to control the peak demand of the house. Considering new smart appliances and internet of things (IOT) applications, the demand response will offer new perspectives on electrical energy generation/consumption and on the operation of power systems.
Keywords: Demand response; smart grid; residential demand control; ENERGY; LOAD; Engineering